বন,বনবিনাশ ও বনবাসীর জীবন সংগ্রাম - Gain, Philip; Khānama, Khādijā; Sarakāra, Lusila; Sāhā, Pārtha Śaṅkara; Majahāra, Pharahāda; Society for Environment and Human Development (Dhaka, Bangladesh) (ঢাকা : সোসাইটি ফর এনভায়রনমেন্ট এন্ড হিউম্যান ডেভেলপমেণ্ট (সেড), 2004)
Contributed articles on forest depletion in Bangladesh and the struggle for survival of adivasis living in the forest districts there; papers presented at a seminar held in Dhaka, Bangladesh in 2003.
Includes bibliographical references.
In Bengali; includes passages in English.
Keywords: Deforestation -- Bangladesh -- Congresses; Forest districts -- Bangladesh -- Congresses; Adivasis -- Suffrage -- Bangladesh -- Congresses